2020
DOI: 10.31545/intagr/125620
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon physical fractions and aggregate stability influenced by land use in humid region of northern Iran

Abstract: The present study was executed in order to examine the influences of land use change on aggregate stability and soil organic carbon fractions in the humid region of the north of Iran. The study area featured three land uses which included natural Hyrcanian forest, tea plantation and paddy rice cultivation. One hundred soil samples were taken from the 0-10 cm layer in a grid pattern to allow for variations in the study area as much as possible in summer 2016. The results revealed that land use change significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In this context, Li et al (2009), Raiesi (2012), and Zhang et al (2012) showed that the balance between the C level of plant residues and the concentration of C through microbial decomposition in soil has a significant effect on SOC and the quality of N. The rates of C inputs through plant remainder are generally changed by land use type and AR (Li et al, 2009). These results are in line with the findings of Li, Liu, et al (2017) and Li, Wen, et al (2017), Lozano‐García et al (2017), and Ayoubi et al (2020). They have shown that in areas with more rainfall, vegetation will be denser, resulting in higher C content in the soil compared with N.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, Li et al (2009), Raiesi (2012), and Zhang et al (2012) showed that the balance between the C level of plant residues and the concentration of C through microbial decomposition in soil has a significant effect on SOC and the quality of N. The rates of C inputs through plant remainder are generally changed by land use type and AR (Li et al, 2009). These results are in line with the findings of Li, Liu, et al (2017) and Li, Wen, et al (2017), Lozano‐García et al (2017), and Ayoubi et al (2020). They have shown that in areas with more rainfall, vegetation will be denser, resulting in higher C content in the soil compared with N.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, the substrate availability was different in differently sized aggregates. The SOC in macro-aggregates from plant and microbial residues is more easily absorbed and utilized by microbial communities [48], but SOC in micro-aggregates with a protective effect is not easy to decompose [49][50][51]. This also explains why the SOC content in micro-aggregates is higher, which is consistent with previous studies [52,53].…”
Section: Linkages Of Soil Aggregate Carbon Components and Microbial C...supporting
confidence: 89%
“…Moreover, soil aggregate is the storage and transformation place of soil nutrients, such as carbon, nitrogen, and phosphorus. In addition, soil microorganisms accumulated in aggregate play an important role in regulating plant growth, reducing hydraulic erosion, and improving soil fertility (Ayoubi et al, 2012;Ayoubi et al, 2020). Different particle size aggregates have different abilities to fix and transform nutrients , which finally affects the geochemical cycle of soil nutrients (Gelaw et al, 2013).…”
Section: Introductionmentioning
confidence: 99%